Illegalisms of Vital Issue. Bodies and Youths in Contexts of Urban Poverty (Andamios, Revista de Investigación Social, 2025)
This paper examines the effects of illegalisms on the lives of young individuals in urban poverty contexts within San Martín district, Buenos Aires province. Drawn from empirical research findings, we propose the conceptual framework of ‘illegalisms of vital issue’, denoting the complex array of practices that systematically expose young students to hazards, gradual bodily deterioration, and imposed ways of living. Our mixed-methods research design integrates in-depth interviews, school assignments, and participant observation in educational and neighborhood settings.
Keywords: Illegalisms; embodied experiences; youth; students; urban poverty